The Anti-cancer Impact of Genetically Engineered Newcastle Disease Virus Expressing GFP Gene Against U87-MG Cell Line - Rasoul, Lubna Muhi (Iraqi Journal of Science, 2023)
A number of disorders characterized by aberrant cell proliferation are referred to as cancers. Cancer is a complicated group of mutagenic diseases that can move or infiltrate to other parts of the body. It develops through a multi-step process. The need for new therapeutic strategies is driven by malignancies resistance to conventional therapies. Use of the Newcastle disease virus as an oncolytic agent has advanced and expanded in immunocompetent carcinoma tumor models by utilizing reverse genetics techniques. Preclinical investigations have shown that recombinant NDV (rNDV-GFP), which expresses foreign genes, is proven to be effective in cancer treatment. Green fluorescent protein gene is usually used as an expression reporter for certain genetically encoded molecular biomarkers. To demonstrate that a gene may be expressed in many organs, interest cells or across an organism, it was utilized to make GFP-expressing biosensors. GFP has been detected in human cells as well as bacteria, yeasts, fungi, fish and other animals. The aim was to investigate the anti-tumor effects of rNDV expressing GFP gene on U78-MG glioblastoma cell line in vitro. This research examined in vitro the anticancer activity of genetically modified Newcastle disease virus strains that express GFP (rClone3-GFP) using the MTT test (a colorimetric assay for measuring cell metabolic activity) on the U87-MG glioblastoma cell line. Recombinant viruses were found to be able to trigger a time-dependent demise of tumor cells death starting 96 hours after inoculation. Using reverse genetics, we inserted GFP-coding regions between the F and HN genes in the lentogenic NDVClone30 strain's genome which was named as rNDV-GFP. The recombinant NDV-GFP strains that produce GFP showed promising results for inhibiting growth of tumor cells. Our study paved the way for the use of recombinant NDV as an anticancer viral vector. Our results suggest that NDV-GFP is a promising therapeutic for glioblastoma cancer treatment.